Adenylyl cyclase type 5 in cardiac disease, metabolism, and aging - Vatner, Stephen F. (American Physiological Society, 2013)
G protein-coupled receptor/adenylyl cyclase (AC)/cAMP signaling is crucial for all cellular responses to physiological and pathophysiological stimuli. There are nine isoforms of membrane-bound AC, with type 5 being one of the two major isoforms in the heart. Since the role of AC in the heart in regulating cAMP and acute changes in inotropic and chronotropic state are well known, this review will address our current understanding of the distinct regulatory role of the AC5 isoform in response to chronic stress. Transgenic overexpression of AC5 in cardiomyocytes of the heart (AC5-Tg) improves baseline cardiac function but impairs the ability of the heart to withstand stress. For example, chronic catecholamine stimulation induces cardiomyopathy, which is more severe in AC5-Tg mice, mediated through the AC5/sirtuin 1/forkhead box O3a pathway. Conversely, disrupting AC5, i.e., AC5 knockout, protects the heart from chronic catecholamine cardiomyopathy as well as the cardiomyopathies resulting from chronic pressure overload or aging. Moreover, AC5 knockout results in a 30% increase in a healthy life span, resembling the most widely studied model of longevity, i.e., calorie restriction. These two models of longevity share similar gene regulation in the heart, muscle, liver, and brain in that they are both protected against diabetes, obesity, and diabetic and aging cardiomyopathy. A pharmacological inhibitor of AC5 also provides protection against cardiac stress, diabetes, and obesity. Thus AC5 inhibition has novel, potential therapeutic applicability to several diseases not only in the heart but also in aging, diabetes, and obesity.